High-Resolution Optical Coherence Tomography in the Differentiation of Inflammatory Versus Noninflammatory Peripheral Corneal Thinning. Issue 1 (January 2017) - Rodriguez, Marianeli; Yesilirmak, Nilufer; Chhadva, Priyanka; Goldhagen, Brian; Karp, Carol; Galor, Anat
Abstract : Purpose: To evaluate whether high-resolution optical coherence tomography (HR-OCT) can aid in differentiation of inflammatory versus noninflammatory causes of peripheral corneal thinning. Methods: Retrospective chart review of 10 patients with peripheral corneal thinning and their respective slit-lamp photographs and HR-OCT images. Results: Ten patients were identified who had peripheral corneal thinning and HR-OCT images. Five had a clinical history consistent with Terrien marginal degeneration (TMD), whereas 5 had thinning believed to be inflammatory in origin. In the eyes with presumed TMD, patients denied pain or inflammation. HR-OCT images demonstrated stromal thinning in the presence of an intact epithelium. The stroma underneath the epithelium in the area of thinning had a similar reflectivity pattern as the nonaffected cornea. There was epithelial marsupialization evident in 2 of the 5 images. In the 4 patients with a clinical history of inflammation (bulbar hyperemia and pain), and in the 1 patient with active inflammation at the time of HR-OCT imaging, HR-OCT also demonstrated thinning with an intact epithelium. In contrast to the TMD group, in the group with signs of inflammation, a dense hyperreflective band was noted in the stroma directly below the epithelium in the area of thinning, suggestive of scarring and/or cellular infiltration. Conclusions: In patients with a clinical history of inflammation and corneal thinning, HR-OCT revealed a hyperreflective band directly under the epithelium in the area of thinning, which was not seen in patients with presumed noninflammatory melts and thinning.